Therapeutic advances of peritoneal dialysis-associated peritonitis - Qiu Deng; Chen Yang; Ning An (Editorial Department of Journal of Clinical Nephrology, 2024)
Peritoneal dialysis-associated peritonitis is a major complication of peritoneal dialysis （PD） in patients with end-stage renal disease （ESRD）. Recurrent peritonitis may lead to peritoneal adhesions and thickening. In severe cases， it results in peritoneal failure so that PD fails with greater morbidity and mortality. Here the definition， epidemiology， risk factors and treatments of peritoneal dialysis-associated peritonitis were summarized with the latest domestic and international researches to provide theoretical rationales for optimized clinical management.